2016
DOI: 10.1111/jgh.13270
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of celiac disease in Asia: A systematic review and meta‐analysis

Abstract: Celiac disease is not uncommon in Asia, and the sero-prevalence and prevalence of CD in Asia are 1.6% and 0.5%, respectively. The prevalence of CD varies with gender and geographic location. There is a need for population-based prevalence studies in many Asian countries to properly estimate the burden of CD in Asia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
81
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 52 publications
4
81
1
1
Order By: Relevance
“…Differences in lifestyle and SEP, including the frequency of intestinal infections, antibiotic use and a variety of dietary factors other than gluten, may lead to differences in the gut microbial flora, thereby affecting the programming of the immune system 15. This so-called hygiene or ‘old friends hypothesis’40 has been linked to the emergence of atopic and autoimmune disease. Individuals living in better hygienic conditions, that is, in urban environments of rich developed countries, face fewer infections during childhood 41.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in lifestyle and SEP, including the frequency of intestinal infections, antibiotic use and a variety of dietary factors other than gluten, may lead to differences in the gut microbial flora, thereby affecting the programming of the immune system 15. This so-called hygiene or ‘old friends hypothesis’40 has been linked to the emergence of atopic and autoimmune disease. Individuals living in better hygienic conditions, that is, in urban environments of rich developed countries, face fewer infections during childhood 41.…”
Section: Discussionmentioning
confidence: 99%
“…It may also be referred to as celiac sprue, glutensensitive enteropathy, or nontropical sprue. [1][2][3][4][5][6][7][8] Early epidemiological studies regarded celiac disease as a disease of individuals of Caucasian ancestry, located mainly in Europe and North America. However, further studies in other areas of the world revealed a similar prevalence of celiac disease there.…”
Section: Definitionmentioning
confidence: 99%
“…5 Meta-analysis conducted by Singh et al found that CD is not uncommon in Asia and the sero-prevalence and prevalence of CD in Asia is 1.6% and 0.5%, respectively. 6 Children with type 1 diabetes, Down's syndrome, autoimmune thyroid disease, Turner syndrome, William's syndrome, IgA degree relatives with CD has increased prevalence in developing this disease. …”
Section: Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of Celiac disease is 2%-3% in Finland and Sweden, 0.2% in Germany [15], 1.6% in Asia [16], and 1% in the United States [17]. The prevalence was 4% in a recent study by Cilleruelo et al [9] who used the HLA-DQ2 test [9].…”
Section: Introductionmentioning
confidence: 99%